Internet Access and Use in Political Discourse by the Members of Parliament in Tanzania - Manda, Paul A; Hilika, Amina R (University of Dar es Salaam Library Journal, 2017)
This paper is based on the research which examined access and use of internet resources and services by the Tanzanian Members of Parliament (MPs) and its impact on the political discourse. The study was conducted in June 2009 among selected parliamentarians. It employed qualitative and quantitative research design. The sample size was 18 parliamentarians and these were selected purposively. The methods of data collection included a questionnaire, interviews and focus group discussion. Analysis of data was mainly descriptive. The key findings of this study are: First, the Parliament Library in Tanzania has made modest investment in ICT infrastructure to support internet access and use. Second, the Library has a good mix of professional and para- professional staff though the level of staffing is not optimum. Third, the Library has a number of important documents and publications available online including the Hansards and reports by various parliamentary committees. Fourth, the MPs have diverse needs although a few of these are central to all the MPs and these include information for debates, information on bills, policies, speeches and constituencies. The demand and need to access the internet resources and services by parliamentarians is on the rise and the parliament, including the parliament library, has to address a number of challenges in connection to this development. The reported challenges include: slow internet connectivity that discourages use; inadequate number of available PCs in the library (only 12 were available); lack of training programme to use the internet and e-resources in general; lack of effective marketing strategies to create awareness of the value of internet resources; low skills and capacities to use the internet resources among the MPs and the library staff; severe time constraint for the MPs to use the library regularly and finally, inadequate library physical space. Detailed suggestions made by the MPs on how these challenges could be addressed are also documented. Generally, the study observes a positive relationship between the use of the internet and increased/improved political discourse and the democratization process. However, one negative impact of the adoption of this new technology by the MPs is an increased knowledge and information gap between those with higher levels of education and the ones with lower levels of education. MPs with higher levels of education are the core group of internet users, while those with lower levels of education are the laggards. The knowledge and information gap is explained by the fact that the MPs with higher levels of education are likely to be better and more informed of significant issues of interest before the adoption of the internet. Thus, the use of the internet will increase and exacerbate this gap even further, unless strategies for intervention (such as training) are implemented. The paper makes a number of recommendations to address these emerging challenges and measures to mitigate negative impacts.